Cotton reinforced biopolymer matrix composite: effect of curing and aging conditions on its mechanical properties - Ahmad, Zuraida; Yusof, Yusliza; Halim, Zahurin; Md. Yusof, Fauziah (Trans Tech Publications, Switzerland, 2011)
The attention in natural fiber reinforced biopolymer composite materials has been rapidly growing both in terms of industrial applications and basic research. This study investigated on the effect of aging time on mechanical properties and morphological structure of thermoset protein-based composites from egg albumen reinforced by natural cotton fibres. The cotton/albumen composites (CAC) were fabricated by hands lay-up technique with 10 w/w % of fiber content. The samples were cured and aged at room temperature for different aging time from 7 to 32 days. The cotton fibres have contributed in a significant improvement in mechanical strength and toughness of the composites. Tensile strength of the composites achieved the optimum strength of 9 MPa after 21 days of aging time and constant till 32 days. As the aging time increased, impact strength of the composites also improved to some value of 20 kJ/m2 . Thereby after 21 days observation, the composites show an equilibrium moisture content of 6-9 wt%, and the strength remains stable at room condition with 50-60% relative humidity (RH). Morphology studied using SEM justify that the moisture content after aging time influenced mechanical properties of the composites.